1979
DOI: 10.1086/130600
|View full text |Cite
|
Sign up to set email alerts
|

The night sky conditions at the Sacramento Peak Observatory. II - Cloud cover, seeing, and precipitable water

Abstract: A summary is given of the following atmospheric conditions at the Sacramento Peak Observatory: cloud cover, seeing, and précipitable water. Sky brightness observations have been reported in an earlier paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The spectrograms centered at 0.55 jam were traced with the PDS microdensitometer at the University of Hawaii and reduced to relative intensity units using appropriate calibration data. A line identification study was undertaken by comparison with the Sacramento Peak Observatory solar flux atlas (Beckers, Bridges, and Gilliam 1976) and with lunar spectra observed and reduced with the same equipment and techniques as those applied to HD 15144. This study revealed the excessive strength of Cr n, and to a lesser extent, Fe n and i, which are characteristic of the blue spectrum.…”
Section: B a Search For The Spectrum Of The Companionmentioning
confidence: 99%
“…The spectrograms centered at 0.55 jam were traced with the PDS microdensitometer at the University of Hawaii and reduced to relative intensity units using appropriate calibration data. A line identification study was undertaken by comparison with the Sacramento Peak Observatory solar flux atlas (Beckers, Bridges, and Gilliam 1976) and with lunar spectra observed and reduced with the same equipment and techniques as those applied to HD 15144. This study revealed the excessive strength of Cr n, and to a lesser extent, Fe n and i, which are characteristic of the blue spectrum.…”
Section: B a Search For The Spectrum Of The Companionmentioning
confidence: 99%
“…Based on direct measurements of the thermal structure parameter C x 2 , the contribution of thé lower ground layer to the total seeing was found to be negligible at night. Beckers et al (1979) have reported seeing measurements from the similar forested summit of Sacramento Peak, which is not too far from Mount Graham but somewhat lower in altitude. They also found very good nighttime seeing conditions which were slightly worse than those reported here.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the Sun can be made to appear point-like by observing its image formed by a distant convex mirror (Edmonds 1975;private communication). In one case a very shortfocal-length lens was used to get a tiny solar image in its entirety into a spectrograph slit (Beckers et al 1976). In another case fiber optics served a similar purpose (Gray 1972).…”
mentioning
confidence: 99%